Batch extraction kinetics and total phenolic content estimation of Syzygium Cumini.L bark. Issue 5 (20th October 2022) - Keerthiga, G.; Sridhar, Adithya
ABSTRACT: Traditional herbs are investigated for their medicinal properties and feasible large scale low cost extraction techniques. The extraction of phenolic content from different plant matrices has been a huge challenge and largely depends on the effectiveness and efficiency of selected extraction methods. The estimation of total phenolic content from Syzygium Cumin.L (Jamun bark) and its optimisation of extraction conditions with respect to nature of solvent, solvent ratios, particle size and solid to solvent ratio were carried out in this study. Room temperature based batch mode of extraction of Syzygium Cumini L bark has been performed and compared with conventional Soxhlet extraction. The total phenolic extraction rate for different ratios of methanol–water and ethanol–water were investigated where methanol–water ratio of 70:30 yields high phenolic extraction rate of 49.22 ± 5.3 mg GAE/g. The particle size of 0.05–0.06 mm, solvent to solid ratio of 3:1 yielded higher total phenolic content of 47.22 ± 3.35 mg GAE/g. The extraction followed second-order kinetics with 98% goodness of fit. Feasible optimised mode of extraction of total phenolic compound shows promising directions towards industrial extraction. GRAPHICAL ABSTRACT: UF0001